Sektor Penerbangan Global dalam Isu Perubahan Iklim : Dampak dan Mitigasinya - Dinar Dewi Kania; Dian Artanti Arubusman; Mustika Sari (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Climate Change is one of the negative impact of globalization which currently challenges  the world community. Climate change is also an important issue in the global aviation sector. However, the growth of  CO2 and Greenhouse Gas emissions from the global aviation sector continues to increase in line with the demand for aviation services. This paper aims to describe the growth of global aviation industry which has an impact on the  increasing of carbon emissions (CO2) trend globally and the mitigation efforts to anticipate weather worsening in the future.  The result shows that the growth of Passenger Kilometer Revenue (RPK) on international flights since 2010 has continued to increase significantly. In general, the global aviation industry (including domestic and international; both passenger and cargo) is estimated to contribute to climate change through 1.9% greenhouse gas emissions (which includes all greenhouse gases) and 2.5% CO2 emissions, and 3. 5% of “Effective Radiative Forcing' (ERF).The reduction of CO2 emissions from the aviation sector includes: 1) improvement of technological efficiency; 2) increased operational efficiency, 3) Use of alternative fuels ,4) change the travel behaviour, etc. Moreover, the mitigation strategies to reduce the impact of AIC (Aircraft-Induced Clouds) in the short term and at low cost can be carried out by operational changes to the aircraft trajectory and adaptation of jet engine fuel.